Pengaplikasian Stiker pada Rancangan Buku Intraktif Kebudayaan Nusantara untuk Anak Kelas 1-3 Sekolah Dasar - Angelina, Angelina; Fuad, Ahmad (UNIVERSITAS SERAMBI MEKKAH, 2025)
To support efficient and effective learning about the culture of the archipelago, especially for children in grades 1-3 of elementary school. An interactive learning media is needed. So the purpose of this research is to produce a sticker media that is applied in an interactive book by describing the culture of the archipelago. This design utilizes a visual approach so that it can attract children to be interested in participating with the media presented. The research method was carried out through stages starting from collecting library data through official journals, reference books, internet facilities, and direct interviewing of informants. The results obtained from this design are the application of stickers to become interactive learning media. This sticker is designed with an emphasis on illustrations adapted for elementary school children. By applying bright color tones accompanied by cute illustrations. Which is then packaged in the form of a book, which discusses the culture of the archipelago starting from clothing, traditional houses, to typical games from all provinces in the archipelago.